INCREASING CALCIUM INTAKE IN YOUNG WOMEN THROUGH GAIN-FRAMED, TARGETED MESSAGES - Jung, Elizabeth Mary (My University, 2004)
The purpose of the present study was to test the effects of message framing and targeted messaging on calcium intake behaviour. Young women who were consuming less than adequate amounts of calcium attended a one-hour seminar, received two pamphlets, one sticker, and one notepad in the mail over the course of one year, all containing information about osteoporosis, bone, and how calcium intake relates to each. Using message framing and targeted messaging as the intervention, participants were randomly assigned to receive the standard care seminar and materials (control), or gain-framed targeted seminar and materials (experimental). Examination of the data revealed that the intervention had significant effects on calcium intake behaviour, and minimal effects on the health belief model (HBM) constructs. No relation was found between HBM constructs and calcium intake. Specifically, using an intent-to-treat repeated measures ANOVA, participants in the experimental condition significantly increased their calcium intake more than those in the control condition over the course of the study (p < .01). All HBM constructs changed over time in both conditions (ps < .05) except for perceived severity (p= .89).Self-efficacy was the only construct to improve significantly more in the experimental condition versus control (p < .01). The HBM predicted calcium intake only during week 25 (p < .01). These findings suggest that it is possible to increase young women's calcium intake consumption through gain-framed, targeted messages. Findings also have important implications for how existing osteoporosis-preventive materials can be improved.